Knowledge sharing and theory of planned behavior: A bibliometric analysis - Muhammad Ashraf, Fauzi; Nguyen, Mai; Malik, Ashish (Emerald Publishing Limited, 2023)
Purpose: The purpose of this study is to review the role of knowledge-sharing and its association with the Theory of Planned Behavior (TPB). TPB is the most used theory in understanding knowledge-sharing behavior in many contexts. Design/methodology/approach: Based on the bibliometric approach, this study extracted and analyzed 229 journal articles on the Web of Science. In addition, two analyses (bibliographic coupling and co-word) were performed to provide science mapping in presenting the knowledge structure on the present and future research direction on knowledge-sharing and TPB. Findings: The findings of this study suggest that two stand-out clusters are determinants and antecedents of knowledge-sharing behavior based on TPB and the role of the virtual platform and social media in facilitating knowledge-sharing among users. Research limitations/implications: This study will benefit researchers and scholars in studying individual behavioral traits underpinning TPB in achieving organizational excellence. Originality/value: This study extends the findings of the previous review because of their limitations on methods. This study confirms the determinants of knowledge-sharing intention and behavior. However, this study suggests integrating TPB with other theories to provide more insights into knowledge-sharing behavior and use online and technology-based platforms to facilitate knowledge-sharing behavior.